2009
DOI: 10.1089/vbz.2008.0141
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of the Crimean-Congo Hemorrhagic Fever Endemic Area in Albania

Abstract: Crimean-Congo hemorrhagic fever virus (CCHFV) is endemic in Albania. Ticks collected from cattle grazing in the endemic areas of Albania were tested for presence of CCHFV RNA, while serum samples collected from goats, cattle, hares, and birds were tested for the presence of specific IgG antibodies to CCHFV. One of the 31 pools prepared, consisting of four female Hyalomma spp. ticks, was found to carry CCHFV RNA with 99.2-100% homology to sequences detected in patients from the same region. Antibodies were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…According to the studies conducted in different countries, CCHFV was found between 1% and 15% in Hyalomma spp. pools (Yashina et al 2003, Papa et al 2009, Sun et al 2009). According to the studies performed using PCR methodologies, in endemic areas in Turkey, CCHFV RNA was found between 3.22% and 10% in pools that consisted of H. marginatum ticks collected from livestock (Tonbak et al 2006, Vatansever et al 2008) and 16.43% in individually tested host-seeking flat ticks collected from the ground (Vatansever et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies conducted in different countries, CCHFV was found between 1% and 15% in Hyalomma spp. pools (Yashina et al 2003, Papa et al 2009, Sun et al 2009). According to the studies performed using PCR methodologies, in endemic areas in Turkey, CCHFV RNA was found between 3.22% and 10% in pools that consisted of H. marginatum ticks collected from livestock (Tonbak et al 2006, Vatansever et al 2008) and 16.43% in individually tested host-seeking flat ticks collected from the ground (Vatansever et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The virus has also been recovered from other thermophilic tick species, including Rhipicephalus ticks in Turkey, Greece and Albania (Yesilbag et al, 2013) (Gargili et al, 2011) (Papadopoulos and Koptopoulos 1978) Papa et al, 2009b) and Dermacentor marginatus in Turkey (Yesilbag et al, 2013).…”
Section: Competent Tick Vectors and Their Geographic Distributionmentioning
confidence: 98%
“…Although mainly an enzootic infection, outbreaks and sporadic small clusters of CCHF cases occur in humans following direct bites of infected ticks, which are competent reservoirs, or via dermal contact with virus-contaminated tissues, blood, or other body fluids of patients or infected domestic ruminants such as cattle, sheep, and goats (Nuttall, 2001). Infected animals are, however, asymptomatic (Papa et al 2009). Humans in high-risk occupations (e.g., slaughterhouse workers, shepherds, health care workers, and veterinarians) are prone to CCHF infection (Garcia et al 2006;Gargili et al 2011;Gunes et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…CCHF infection mainly circulates in rural areas. Like all other vector-borne diseases, the presence and persistence of zoonotic foci of infection depends on the biological and ecological relationships between three very different kinds of organisms: virus, tick, and vertebrate host (Papa et al 2009). Although CCHF virus has been isolated from several species of hard ticks (Ixodidae), the main group of vectors appears to be ticks of the genus Hyalomma (Nabeth et al 2004).…”
Section: Introductionmentioning
confidence: 99%